Popularizability, semiotic syncretism and poetic function in “Bullerengue”, by J. Artel and J. A. Rincón, played por Cantatutti - Nadal García, Icíar; Fernández Amat, Carmina (Tropelías: Review of Literary Theory and Comparative Literature, 2020)
This work analyzes the dynamic semiotic structures and the functions of a piece of music and its interpretation: “Bullerengue. Colombian rhythm”. The discursive cultural tradition in which the score arises is studied: its lyrics, its music and its “signed” interpretation, music translated and interpreted in the Spanish sign language (LSE).The multiple levels of their syncretism or intermediality, and their interaction, are considered, especially when performed by the Cantatutti choir. Poetic links of text and music are especially analyzed.
Keywords: Intermediality; syncretic discourse; semiotics of music; semiotics of musical interpretation; signed music; music translated and interpreted in the sign language; bullerengue